Characteristics of Work Stress and Effect the Performance of Employees (Empirical Studies in Kampong Batik Laweyan Surakarta) - Hakim, Lukman; Sugiyanto, Eko (Universitas Muhammadiyah Surakarta, 2015)
This study aimed to: (1) identify the characteristic of work-stress in Kampong Batik Laweyan Surakarta, (2) analyze the cause and effect of the characteristic of work-stress toward job performance in Kampong Batik Laweyan Surakarta. The location of research is in Kampong Batik Laweyan. The objects of this study are work-stress as the independent variable and employee performance as the dependent variable. This research is descriptive research and verification. The total populations in this study were 121 employees, of which based on sampling technique applied, as many as 100 employees were taken. The data were collected with interviews, open questionnaires, and documentation. The data were analyzed repeatedly through regression analysis. The findings show that all characters of work-stress have negative effect toward job performance. The variables are (1) environment-stress,(2) organization-stress and (3) individual-stress.